L1 retrotransposons are transcriptionally active in hippocampus of rat brain - Mukherjee, Somnath; Sharma, Deepak; Upadhyaya, Kailash C (Prague Medical Report, 2016)
LINE1 (L1) is an autonomous, non-LTR retrotransposon and the L1 family of retrotransposons constitute around 17%, 20% and 23% in the human, mouse and rat genomes respectively. Under normal physiological conditions, the retroelements remain by and large transcriptionally silent but are activated in response to biotic and abiotic stress conditions and during perturbation in cellular metabolism. They have also been shown to be transiently activated under certain developmental programs. Using RT-PCR, we show that the L1 elements are transcriptionally active in the hippocampus region of the brain of four-month-old rat under normal conditions without any apparent stress. Twenty non-redundant LINE1-specific reverse transcriptase (RTase) sequences form ORF2 region were isolated, cloned and sequenced. Full length L1 element sequences complementary to the isolated sequences were retrieved from the L1 database. In silico analysis was used to determine the presence of these retroelements proximal (up to 10 kb) to the genes transcriptionally active in the hippocampus. Many important genes were found to be in close proximity of the transcriptionally active L1 elements. Transcriptional activation of the elements possibly affects the expression of the neighbouring genes.
Keywords: Hippocampus; krysa rodu Rattus; Rats; Transcriptional Activation; aktivace transkripce; sekvenční analýza; Long Interspersed Nucleotide Elements; dlouhé rozptýlené jaderné elementy; hipokampus; zvířata; Sequence Analysis; reverzní transkriptasa; RNA-Directed DNA Polymerase; Animals